Delayed presentation of complex complete dorsal thumb metacarpophalangeal joint dislocation: a difficult case to manage and review of literature - Pandey, Praveen Kumar; Pawar, Inder Prakash (International Surgery Journal, 2017)
Metacarpo-phalangeal (MCP) joint dislocation is a rare occurrence which commonly involves index and little finger. Thumb MCP joint dislocation is a pretty rare pathology. MCP joint dislocations are classified into dorsal or volar types. They are further categorized as incomplete, simple complete and complex complete. Complex complete MCP joint dislocation requires surgical reduction most of the times because of tissue entrapment in joint. In the present case report, a case of two and a half months old complex complete thumb MCP joint dislocation left in 18-year old male encountered which was irreducible by closed means and required surgical intervention. Dorsal hand surgical approach was utilized for reduction of dislocation. This unusual, difficult and rare case of two and a half months old complex complete dorsal dislocation of the thumb MCP joint is presented in this case report.